2012
DOI: 10.4172/2161-0711.1000152
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Genetic Testing Awareness, Attitudes and Intentions of Latinas Living along the US-Mexico Border: A Qualitative Study

Abstract: Background Genetic testing for breast cancer may facilitate better-informed decisions regarding cancer prevention, risk reduction, more effective early detection, and better determination of risk for family members. Despite these potential benefits, significant portions of the US population—particularly Latinas—lack awareness of genetic testing for breast cancer susceptibility. Among women who are tested, less than 4% are Latina. To uncover reasons for Latinas’ low participation, this study explores awareness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Overall, men in this study supported the use of a mailed letter for communicating genetic risk, supporting prior findings for this method of delivery (30). In addition, the Spanish speaking men highlighted the importance of receiving results in their preferred language, as has been previously reported in studies centered on BRCA1/2 (14,17). Mexican-origin men expressed their interest in having an optional appointment with either a study staff member or a health professional with sufficient knowledge on PNPLA3 and its influence on NAFLD progression.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, men in this study supported the use of a mailed letter for communicating genetic risk, supporting prior findings for this method of delivery (30). In addition, the Spanish speaking men highlighted the importance of receiving results in their preferred language, as has been previously reported in studies centered on BRCA1/2 (14,17). Mexican-origin men expressed their interest in having an optional appointment with either a study staff member or a health professional with sufficient knowledge on PNPLA3 and its influence on NAFLD progression.…”
Section: Discussionsupporting
confidence: 85%
“…While the importance of genetic testing has recently emerged within the context of personalized medicine, there have been limited studies on genetic testing strategies for Mexicanorigin adults and no studies to date specifically for men (13)(14)(15)(16)). However, low levels of knowledge and awareness about genetic testing have previously been reported (16), and prior findings demonstrate that Hispanics may not understand risk within the context of genetics due to limited genetic literacy defined as the ability to obtain, process, understand, and use genetic information (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Culture-specific stigma, shame, and secrecy about intractable illnesses, particularly cancer, can prevent sharing disease-related information in Latinx families (Joseph & Guerra, 2015). Studies of cancer prevention reported that Latinx populations avoided screening because of fatalismo (fatalism), a sense that the disease trajectory was determined by fate, and that little could be done (Chalela et al, 2012;Kinney et al, 2010;Rajpal et al, 2017;Sussner et al, 2013Sussner et al, , 2015.…”
Section: Religion Fatalism or Disease Stigmamentioning
confidence: 99%
“…Among this group, only 1–4% of women had BRCA testing performed even though most of them declared they would undergo genetic testing within six months if it was offered free of cost. 74 …”
Section: Genetic Riskmentioning
confidence: 99%